2004
DOI: 10.1080/02844310410029084
|View full text |Cite
|
Sign up to set email alerts
|

Injuries to children's hands caused by the engine belts of agricultural machines: classification and treatment

Abstract: Injuries to children's hands with farm machinery, particularly tractors, are common in rural areas. We present 58 cases of hand injuries in children aged from 3 to 7 (mean 4.5), caused by the engine belts of agricultural vehicles, who were referred from the cities in Central Anatolia. The injury patterns among patients were similar. The injury generally starts from the middle phalanx of the third finger, crosses the proximal phalanx of the fourth finger and ends in the hypothenar region. The patients were cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…3,5,11,16 This rate was 13.8% (70/437) in our study. This difference was likely associated with the location of our hospital in a metropolis and also with being the reference center for hand injuries.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…3,5,11,16 This rate was 13.8% (70/437) in our study. This difference was likely associated with the location of our hospital in a metropolis and also with being the reference center for hand injuries.…”
Section: Discussionmentioning
confidence: 64%
“…Although, there are several studies analyzing epidemiology of hand injuries in children conducted in different countries and geographic regions, similar injury patterns seem to occur. 3,5,[16][17][18][19][20][21] The most common cause of outdoor injuries was pinching in the front door of house or school. Most (80%) injuries occurred between 14:00 and 20:00 pm.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,6,14] Although there are a few articles in the literature about the classification of upper extremity injuries due to farming machines, since the present classifications do not cover all cases and an appropriate treatment algorithm cannot be created as a result of these classifications, new classifications are still necessary. [4,6,11,13] Maxim et al [6] reported three types of severe hand in-58 Ocak -January 2012 April 1 1 May 3 3 June 2 1 3 July 1 1 2 August 3 1 3 4 11 September 1 2 2 5 Total 5 2 3 3 10 2 25 Table 4. Admission year and degree of trauma among patients Years 1st degree 2nd degree 3rd degree 4th degree 5th degree 6th degree Total 2007 1 1 1 3 2008 2 1 4 7 2009 2 3 2 6 2 15 Total 5 2 3 3 10 2 25 juries due to corn-picker accidents in their study reported in 1954.…”
Section: (Color Figures Can Be Viewed In the Online Issue Which Is Amentioning
confidence: 99%
“…In this type of classification, there were no data about the involved tissue in the injury (bones, tendons, nerves, vessels, etc). In 2004, Terzioglu et al [13] suggested classifying the hand injuries due to farming machines as 1st degree: soft tissue injury; 2nd degree: degree 1 + tendinous injury; 3rd degree: degree 2 + bony injury; 4th degree: degree 3 + vascular and nerve injury; and 5th degree: amputation. In our opinion, the most appropriate classification among the reported classifications on this topic seems to be the classification of Terzioglu et al However, this classification does not cover all cases.…”
Section: (Color Figures Can Be Viewed In the Online Issue Which Is Amentioning
confidence: 99%
See 1 more Smart Citation